ASSESSING THE IMPACT OF DIFFERENTIATED INSTRUCTION ON ENHANCING STUDENTS’ SPEAKING PROFICIENCY - Nurelviani, Destia; Prastyo, Yanuar Dwi (JIMR : Journal Of International Multidisciplinary Research, 2024)
The primary goal is to assess how differentiated instruction influences students' fluency, pronunciation, and vocabulary acquisition in English. The research employs a quasi-experimental one-group pretest-posttest design, involving 13 eleventh-grade students selected through purposive sampling, focusing on those with initial difficulties in speaking. The study progresses through three stages: initial observation and pre-test, structured differentiated instruction intervention sessions, and a post-test to measure improvements. Findings show a significant improve ment in speaking skills, with a mean difference of 2.48 between pretest and posttest scores, supported by a p-value of 0.00, indicating the effectiveness of differentiated instruction. The greatest improvement was observed in vocabulary, followed by comprehension and gram mar. Despite the study's limitations, such as a small sample size and lack of a control group, the results underscore the potential of differentiated instruction as a valuable teaching strategy for addressing individual learning needs. These findings suggest that differentiated instruction can be an effective approach for enhancing English language proficiency in diverse classroom settings.